Arthur Miller's Death of a salesman - Hays, Peter L., 1938-; Nicholson, Kent (Continuum modern theatre guides., 2008)
Every day, in some part of the world, an Arthur Miller play is performed. In the nearly 60 years since its first production, the Pulitzer Prizewinning Death of a Salesman has been become a classic, a staple of school anthologies of American literature and of acting companies'' repertoires. It has received worldwide productions, whether as a study of parent-child relationships, as in its landmark 1976 production directed by Miller in Beijing, or as a critique of Western capitalism and has been filmed once for television and twice for movies.